The Effects of Price Promotions on Consumers's Perceived Value and Purchase Intention - Hsu, Yung-Fen (2008)
Price promotions are widely used to increase sales in today's competitive markets; however, the negative effects may result if they are not properly applied. Hence, this paper seeks to explore how price promotions affect consumers'perceived value and purchase intention so as to assist marketers to maximize the benefits and minimize the weakness of price promotion activities. This paper will provide a systematic overview of price promotion issues such as reference prices, semantic cues and perceived value, combined with the research of in-depth interviews with international students. Through the findings, it has been proved that reference prices and the framing of price promotions have great correlation with consumers'perceived value and thereby their buying intention, which may also be affected by different product price levels.